Improving Student Learning Outcomes Using Crossword Based Worksheet In Primary Schools - Oktavia, Mitra; Hiltrimartin, Cecil; Wati, Destieana (Journal of Basic Education Research, 2023)
Purpose of the study: This research aims to improve student learning outcomes by using TTS-based LKPD in the learning process. Methodology: This research was carried out in class IV.B of Elementary School 7 Palembang in the science and sciences subject. The research method used is classroom action research. The population and sample in this study were all class IV students at SDN 07 Palembang. The data collection techniques used by researchers are observation and tests. The data analysis technique used is qualitative analysis and quantitative analysis. Main Findings: The results of research using TTS-based LKPD in science and science subjects in class IV can improve student learning outcomes with results in cycle I as much as 45.4%, cycle II as much as 81.8%, and cycle III as much as 88.4% as well as post-test 95.4% with a student completion target of 85%. Novelty/Originality of this study: TTS-based LKPD can improve student learning outcomes in class IV science and science subjects at Elementary School 7 Palembang.